A New Technique to Identify Arbitrarily Shaped Noise Sources - Roberto A. Tenenbaum; Marcelo Bruno S. Magalhães (Shock and Vibration)
Acoustic intensity is one of the available tools for evaluating sound radiation from vibrating bodies. Active intensity may, in some situations, not give a faithful insight about how much energy is in fact carried into the far field. It was then proposed a new parameter, the supersonic acoustic intensity, which takes into account only the intensity generated by components having a smaller wavenumber than the acoustic one. However, the method is only efective for simple sources, such as plane plates, cylinders and spheres. This work presents a new technique, based on the Boundary Elements Method and the Singular Value Decomposition, to compute the supersonic acoustic intensity for arbitrarily shaped sources. The technique is based in the Kirchoff-Helmholtz equation in a discretized approach, leading to a radiation operator that relates the normal velocity on the source's surface mesh with the pressure at grid points located in the field. Then, the singular value decomposition technique is set to the radiation operator and a cutoff criterion is applied to remove non propagating components. Some numerical examples are presented.